Healthcare-associated malaria: a systematic review, 1997 to 2023 - Gossner, Céline M; Hallmaier-Wacker, Luisa K; Noel, Harold; Fernández Martínez, Beatriz; Pervanidou, Danai; Tseroni, Maria; Enkelmann, Julia; Boccolini, Daniela; Plachouras, Diamantis (Euro surveillance : bulletin européen sur les maladies transmissibles, 2025)
BackgroundMalaria is primarily transmitted through mosquito bites; occasionally, direct transmission through blood has been reported. Healthcare-associated infections refer to infections acquired in a hospital or another healthcare setting.AimThis systematic review aims to explore determinants of healthcare-associated malaria (HAM) cases.MethodThis review follows the PRISMA guidelines and was registered in PROSPERO (CRD42022309701). We searched five databases for publications on HAM cases published between 1 January 2000 and 7 December 2023. We initiated a data call for HAM cases to public health authorities from 37 European countries. We performed a backward and forward search, reviewed health authorities' websites, performed searches on Google and the European Scientific Conference on Applied Infectious Disease Epidemiology (ESCAIDE) conference abstracts book.ResultsWe identified 37 studies on HAM comprising 55 HAM cases, of which 35 (64%) were infected in Europe, primarily in Spain (nine cases), France and Italy (seven cases each). All cases were infected with except one individual. Fifty HAM cases were hospital inpatients and five were healthcare workers. Five patients died. Flushing of vascular catheters with contaminated heparin/saline solution and manipulation of intravenous catheters were the most frequently reported procedures leading to infection among patients.ConclusionsWhile rare, HAM transmission can be fatal. Healthcare-associated malaria is preventable through strict adherence to infection prevention and control procedures. Despite extensive investigations, the procedure leading to infection often remained unknown, highlighting the complexity of investigations. Guidance and protocols for conducting investigations may improve the success rate of such inquiries.